Nominal and Actual Values of Inductor and Capacitor Parameters at High Frequencies - E. V. Gurov; S. S. Uvaysov; A. S. Uvaysova; S. S. Uvaysova (Российский технологический журнал, 2019)
Coil inductance and capacitor capacitance depend on overall dimensions, structure, and ambient factors. They do not vary with frequency. Reactive component impedance is determined by inductance or capacitance respectively, if active resistance is not considered. This is true for the frequencies which are significantly lower than the self-resonant frequency of the component. Parasitic parameters contribution increases on approaching the self-resonant frequency. Therefore, the componentʼs actual inductance and actual capacitance on operating frequency are defined. They are provided by manufacturers and differ from the nominal values. The actual values provide more accurate impedance of components near the considered frequency. Significant deviation from the considered frequency can cause impedance mismatch even more than the nominal values can provide. Frequency response of the high-frequency circuits such as analog filters and impedance match networks are determined by components impedance, not the nominal values. Thus, calculated values must be close to the actual values. The purpose of this article is to justify actual values application instead of nominal values.